Enhancing income of marginal and small FFP farmers through improved agro-techniques through Improved Agro-techniques of coriander and garlic - Singh, Ishwar; Choudhary, B R; Singh, S K; Kumar, Mahendra; Kumari, Shilpa; Singh, Garbar; Sarita, Sarita (Indian Farming, 2021)
Small and marginal farmers require continuous income for their livelihood security. Labour intensive bulb crop and high value seed spices are grown by farmers in the Farmer FIRST Programme (FFP) villages of Jodhpur District in Rajasthan. Poor and illiterate farmers are still unaware about the improved agro-techniques available to raise production and quality of their crop. To improve income and appraise the new agro-techniques of seed spices and bulb crops, 75 demonstrations were carried out during 2018-19 and 2019-20 on coriander and garlic. The results revealed that these demonstrations were proven effective in spreading the beneficial effect of potash, IPM and improved varieties of bulb and seed spice crop.